Effectiveness of Board Book and Pop-Up Book Media in Health Education for Toilet Training among Children with Intellectual Disabilities - Nurul Fahmi Rizka Laily; Esa Rosyida Umam; Lilis Fatmawati; Merlin Septianti (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Background: Children with intellectual disabilities often face challenges in carrying out toilet training due to limitations in cognitive abilities and adaptive skills. Therefore, alternative learning media such as board books and pop-up books, which have been proven effective in visual learning, are needed. This study aims to determine the differences in the effectiveness of health education using board book media and pop-up book media on toilet training in children with intellectual disabilities.Methods: This study used a quasi-experimental design with a two-group pretest–posttest approach. A total of 23 children with intellectual disabilities were included using a total sampling technique. Participants were divided into two groups based on class, namely the board book group and the pop-up book group. Data were collected using questionnaires and observation sheets, then analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test.Results: The Wilcoxon test results showed a significant improvement in knowledge, attitudes, and toilet training skills before and after health education in both groups (p < 0.001). Meanwhile, the Mann–Whitney test showed no statistically significant difference in effectiveness between the board book and pop-up book media (p > 0.05).Conclusion: This study concludes that both board book and pop-up book media are effective in improving knowledge, fostering positive attitudes, and enhancing toilet training skills among children with intellectual disabilities. Statistical analysis also showed no difference between the two intervention media, indicating that each medium has comparable potential for use in health education programs.